Optimal bubble deck slabs in regard to ultimate and serviceability limit states - Staszak, Natalia; Gajewski, Tomasz; Garbowski, Tomasz (Computer Assisted Methods in Engineering and Science; Online First, 2025)
This article explores innovative approaches to the design of reinforced concrete bubble deck slabs. The primary objective is to achieve weight minimization while ensuring compliance with both ultimate limit state (ULS) and serviceability limit state (SLS) requirements. Advanced numerical homogenization techniques and a general nonlinear constitutive law (GNCL), within a finite element method (FEM) framework are employed to perform rapid and precise structural analysis. The study addresses the environmental impacts of traditional construction methods, emphasizing the need for sustainable design practices. By introducing voids into the structural elements of the deck slab, the research aims to reduce material consumption without compromising structural integrity. The optimization process involves identifying optimal design parameters, including the size of the bubble deck unit and the dimensions of the bubbles, to balance material efficiency and structural performance. Computational verification demonstrates that the proposed method accurately predicts displacements and stresses when compared to full 3D models. The results highlight the potential for significant material and cost savings, as well as a reduced environmental impact. The study concludes that the combination of numerical homogenization and GNCL offers a robust and flexible tool for the optimal design of reinforced concrete bubble deck slabs, offering a sustainable alternative to traditional construction methods.